BIAS GENDER DALAM NASKAH ADᾹB AL-MAR’ᾹH KARYA KH. MA’MUR NAWAWI (KAJIAN TEORI FEMINISME) - Zahra Taslitsiyah Khoirunisa; Akmaliyah Akmaliyah; Mawardi Mawardi; Amiq Amiq (Jurnal Anifa: Studi Gender dan Anak, 2022)
The issue of gender is still an interesting thing for literary researchers if it is associated with Islamic discourse, which will effectively influence various social, cultural, and even political changes. Problems that arise from a gender perspective focus on the social aspect that sees differences in human sexuality in their position in society. Likewise, one of the manuscripts, a cultural heritage, invites literary critics to analyze the critical study of the text of the Adābu Al-Mar'āh manuscript using the perspective of feminism theory. This research aims to analyze other gender-biased texts in the Adābu Al-Mar'āh manuscript. The research method used is the content analysis method with a qualitative approach or research that refers to the analysis of data linked to a problem to be investigated to produce a conclusion. In this manuscript, several text fragments are in the text that direct gender bias in the household environment. Gender biases in this text include; marginalization or restriction of the wife, gender stereotypes, and subordination or subordination of a wife. This is due to the view of inferiority toward a wife, including the wife who is considered a domestic role in the family, the wife only as a companion to the husband, and the wife who only has a role as a housewife.